Intelligent Cutter Suction Dredging Using the Logic Based Framework LPS - Sadri,F (CEUR, 2016)
LPS (Logic-based Production System) is a framework that combines logic programs with reactive rules and a destructivelyupdated database. The logic programs provide proactive behavior and allow definitions of processes, and the reactive rules provide reactive behavior. This paper describes a first attempt in using LPS to model the operations of cutter suction dredging (CSD). It is the result of a year-long consultation with experts from the Dredging Engineering Research Centre at Hohai University. LPS was chosen for this application because its combination of proactivity and reactivity was thought to be a good match for CSD operations. These require processes for normal operations, as well as constant monitoring to identify any operational problems that may be arising and taking reactive correction steps.